VARIASI OPTIMUM BIOGAS DARI LIMBAH CAIR KELAPA SAWIT - Budi Nining Widarti; Ditha Dwijayanti; Edhi Sarwono (Universitas Lambung Mangkurat, 2023)
Biogas is one of the renewable energy sources produced from the process of methanogenesis. This research was conducted to determine the optimal composition of palm oil liquid waste (POME) and cow rumen fluid to produce biogas and to determine the effect of the composition of the mixture on the volatile solid value, pH, temperature, biogas production, and flame testing. This study used 3 trial batch type digesters with a capacity of 40 L and the raw material was a mixture of palm oil mill effluent (POME) and cow rumen fluid with a composition of 3 : 1 (R1), 1 : 1 (R2) and 4 : 1 ( R3). During the treatment, pH, temperature, VS and biogas were tested. This research was conducted for 49 days. The research was conducted for 49 days and it was found that the composition of the mixture of palm oil mill effluent (POME) with cow rumen fluid which was optimal for producing biogas was found in R1 with a mixture composition of POME: cow rumen fluid as 3:1. R1 produces a volume of biogas of 1.86 L, from the flame test it can ignite from the third to the seventh week. The composition of the different mixed ingredients for each digester has an influence on the value of VS, pH, temperature, biogas production, and flame tests. The effect was on the difference in VS values, pH, biogas production, and flame test results for each digester, but for the temperature parameter the effect was not too visible because the temperature ranges for the three digesters were both in the mesophilic temperature range, ranging from 27°C - 32°C.